2021
DOI: 10.1088/1755-1315/733/1/012093
|View full text |Cite
|
Sign up to set email alerts
|

The Indonesian coffee consumers perception on coffee quality and the effect on consumption behavior

Abstract: The main issue of coffee commodity in Indonesia besides productivity is quality consistency. Defective coffee has a low quality level as well as low selling value and potentially detrimental for the coffee industry. However, despite its potential impact on coffee consumption behavior, the study on coffee quality based on Indonesian consumer perspectives is still limitedly published. This study aimed to investigate Indonesian coffee consumer perception on coffee quality and the effect on consumption behavior. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
3
0
3
Order By: Relevance
“…On the other side, coffee with milk is more likely to be drunk by women (p=0.00001), similar to our survey. According to Sunarharum et al [9], the majority of coffee consumers in Indonesia drink instant coffee (32%), ice coffee with milk (30%), and coffee mixed with milk (38%), which is the most popular choice among the panelists.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other side, coffee with milk is more likely to be drunk by women (p=0.00001), similar to our survey. According to Sunarharum et al [9], the majority of coffee consumers in Indonesia drink instant coffee (32%), ice coffee with milk (30%), and coffee mixed with milk (38%), which is the most popular choice among the panelists.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the value of Pearson's coefficient (0.26), measuring the intensity of dependence, we can confirm a weak dependence. According to Sunarharum et al [9], analysis of the location or where respondents drink coffee in Indonesia revealed that onsite drinking (or drinking in coffee shops or cafes) is preferred mostly by the more experienced group, as opposed to common consumers who prefer a takeaway method and consume coffee at home. According to Czarniecka-Skubina et al [4], the majority of Polish consumers consume coffee at home (95.5%) and at work (79.7%).…”
Section: Resultsmentioning
confidence: 99%
“…(2020), Indonesia menempati peringkat keempat sebagai produsen kopi dunia setelah Brasil, Vietnam, dan Kolombia. Saat ini Indonesia menjadi konsumen kopi potensial seiring dengan semakin populernya kopi lokal Indonesia, sehingga produksinya juga meningkat untuk memenuhi permintaan kopi lokal dalam negeri (Sunarharum et al, 2021).…”
Section: Organizationunclassified
“…Hal ini membuat kopi di Indonesia menjadi sumber daya alam yang memiliki nilai jual untuk dikembangkan. Kini berbagai macam produk kopi sudah banyak diperjual belikan, mulai dari produk kopi bubuk hingga minuman kopi instan dengan berbagai varian rasa dan kemasan (Elang dan Vidaksa, 2018) Produk kopi memiliki aroma serta cita rasa yang unik, dan telah disukai banyak orang di seluruh dunia (Tamkaew et al, 2021). Minuman kopi merupakan salah satu minuman paling populer di kalangan masyarakat Indonesia (Suisa et al, 2014).…”
Section: Organizationunclassified
“…Coffee has been one of the most popular beverages appreciated for centuries due to its hedonistic and stimulating properties [1,2]. Indonesia is the fourth largest coffee-producing country in the world after Brazil, Vietnam, and Colombia and the second largest coffee-consuming country after Brazil [3,4]. Data compiled by the International Coffee Organization (ICO) in 2019 showed increased coffee consumption in Indonesia, with an average increase of 2.5 % yearly since 2010.…”
Section: Introductionmentioning
confidence: 99%